2019
DOI: 10.2139/ssrn.3425768
|View full text |Cite
|
Sign up to set email alerts
|

Divided We Stand? Professional Consensus and Political Conflict in Academic Economics

Abstract: In this paper we address the issue of the role of ideology and political preferences of publically engaged economists and contribute to the debate on consensus in economics. To do so, we conduct a social network analysis on the signatories of economist petitions, which we identify as one channel for economists to exert public influence. We base our analysis on a sample of 77 public policy petitions and presidential anti-/endorsement letters from 2008-2017 in the United States with more than 6,400 signatories a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…When past evidence is less extensive, differences in opinions do show up." 8 They also find that "there is no evidence to support a conservative versus liberal divide among these panel members, at least on the types of questions included so far in the surveys." 9 Van Gunten et al (2016) suggest that Gordon's and Dahl's focus on testing factionalism, which reduces the social structure of the discipline to discrete and mutually exclusive group memberships, is a poor model for economics.…”
Section: Economics and Ideology: A Brief Overviewmentioning
confidence: 96%
“…When past evidence is less extensive, differences in opinions do show up." 8 They also find that "there is no evidence to support a conservative versus liberal divide among these panel members, at least on the types of questions included so far in the surveys." 9 Van Gunten et al (2016) suggest that Gordon's and Dahl's focus on testing factionalism, which reduces the social structure of the discipline to discrete and mutually exclusive group memberships, is a poor model for economics.…”
Section: Economics and Ideology: A Brief Overviewmentioning
confidence: 96%
“…Finally, there is compelling evidence that economists make policy assessments and give policy advice in accordance with their own ideological positions. When the profession is rather uniform in its worldviews, perspectives, and understandings of poverty, this means that policy advice and public engagement are likely one-sided and biased (Horowitz and Hughes, 2018;Beyer and Pühringer, 2019). In particular, a recent study by Banuri et al (2019) brought to light cognitive biases of development professionals (see also World Bank, 2015).…”
Section: Epistemic Injustices and Research Qualitymentioning
confidence: 99%
“…However, as recent studies on the public policy views of prominent economists showed that the support for trade liberalisation to increase potential economic welfare is a rather consensus position among economists (e.g Gordon andDahl 2013, Beyer andPuehringer 2019). Hence only about 5 per cent of the respondents of a survey among economists disagreed with the statement that 'tariffs and import quotas usually reduce general welfare' (Fuller and Geide-Stevenson 2014, p. 134).…”
Section: On Trade Debate(s) In the Economics Professionmentioning
confidence: 99%